Si/Cu composite as anode material for lithium-ion batteries - Zeng, Hong; He, Yawen; Chamas, Mohamad (Frontiers in Energy Research, 2022)
Si/Cu composite anode was prepared through a facile solid mechanosynthesis method and wet chemical etching. Phase transition, morphologies were investigated on pristine and as-synthesized composites. Effects of presence of Al80Si20, super P carbon on ball-milling was investigated. Moreover, the etching effect was compared on pristine Cu-Zn and composites by addition of NH4Cl. The results of X-ray diffraction patterns, scanning-electron-microscopy morphological images and focus-ion-beam/ energy-dispersive mapping demonstrated that the formation of the intermetallic, elemental distribution, homogeneity and dezincification are involved with the addition of Al, super P carbon, etching additive NH4Cl. Super P carbon avoided the formation of Cu-Si while Al made the more homogenous distribution of Si/Cu. The synthesized two types of Si/Cu composites deliver specific capacity/retention rate of 678 mAhg-1/79.3% (Si/Cu from pure Si) and 750 mAhg-1/86.2% (Si/Cu from Al80Si20) at 100th, respectively. The higher stability of the galvanostatic cycling and capability performance were resulted from the homogeneity of Si and Cu.